Variation among cowpea genotypes in sensitivity of transpiration rate and symbiotic nitrogen fixation to soil drying - Sinclair, Thomas R.; Manandhar, A.; Belko, N.; Riar, M.; Vadez, Vincent; Roberts, P.A. (Wiley, 2015)
Cowpea (Vigna unguiculata L. Walp.) is often considered a crop species appropriate for drier environments. However, little or no information exists on two key physiological traits for drought conditions: early decrease in transpiration rate in the soil drying cycle and sustained N fixation activity under low soil‐water conditions. In this study, the responses of these two traits to soil drying were compared among 10 genotypes. The fraction of transpirable soil water at which transpiration rate began to decline varied from 0.59 to 0.24. The genotypes with the higher thresholds for the transpiration decrease offer a conservative water use strategy during soil drying and, hence, may be especially appropriate for very dry areas. The fraction of transpirable soil water at which N fixation rate began to decline ranged from 0.33 in one line to another line in which there was no decline in N fixation rate. Five lines had especially low thresholds for the decline in N fixation rate, which would be highly desirable in arid areas. In fact, N fixation tolerance to drought in these five lines is superior to any responses observed in other grain legumes. There was no correlation between the thresholds for decline in transpiration and N fixation.